Wealth effect of Islamic bond offering announcement (Table of contents and abstract only) - Nasyra Ab Jamil (2007)
In this study the wealth effect of Islamic bond offering announcement was investigated using a firm's data from 2001 to 2005. Three types of Islamic Bonds were examined: Mudharabah, Al-Bai Bithamin Ajil and Ijarah. The results show that there no significant positive abnormal return occurs following an Islamic bond offering announcement. The findings revealed that Malaysian investors respond positively to these announcements, perceiving them as good, thus creating a positive wealth effect. This positive effect is consistent with the findings of Chang(2004) and suggests that Islamic bond financing is a means of minimizing the cost and increasing the opportunity of investment when value and timing are uncertain. (Author's abstract)